2011
DOI: 10.1186/1471-2164-12-530
|View full text |Cite
|
Sign up to set email alerts
|

Conjugating effects of symbionts and environmental factors on gene expression in deep-sea hydrothermal vent mussels

Abstract: BackgroundThe deep-sea hydrothermal vent mussel Bathymodiolus azoricus harbors thiotrophic and methanotrophic symbiotic bacteria in its gills. While the symbiotic relationship between this hydrothermal mussel and these chemoautotrophic bacteria has been described, the molecular processes involved in the cross-talking between symbionts and host, in the maintenance of the symbiois, in the influence of environmental parameters on gene expression, and in transcriptome variation across individuals remain poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 82 publications
3
20
0
Order By: Relevance
“…In addition, metal accumulation in gills and digestive glands can be related to the nutrients uptake process from symbiotic bacteria. Provannid snails and mytilid mussels found in hydrothermal vent fields commonly harbor chemoautotrophic bacteria (methane-and sulfide-oxidizing bacteria) (Podowski et al, 2009(Podowski et al, , 2010Boutet et al, 2011;Duperron et al, 2011;Beinart et al, 2012;Rodriguez et al, 2013;Sen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, metal accumulation in gills and digestive glands can be related to the nutrients uptake process from symbiotic bacteria. Provannid snails and mytilid mussels found in hydrothermal vent fields commonly harbor chemoautotrophic bacteria (methane-and sulfide-oxidizing bacteria) (Podowski et al, 2009(Podowski et al, , 2010Boutet et al, 2011;Duperron et al, 2011;Beinart et al, 2012;Rodriguez et al, 2013;Sen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These bacteria receive all metabolites necessary for chemoautotrophy from the surrounding seawater -a mix between deep-sea water and hydrothermal fluid -through the bivalve gills, which maintain a flux usually serving nutrition by filtration. This symbiosis is known to be plastic and highly dependent on environmental conditions (Colaço et al, 2002;Fiala-Médioni et al, 2002;Salerno et al, 2005;Duperron et al, 2006;Boutet et al, 2011). Indeed the lack of hydrogen sulphur or methane can lead one or the other type of symbiont to take precedence on the other.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Halary and co-authors showed that a high concentration of hydrogen sulphur, in mussels kept in aquaria, induces a higher level of sulphur-oxidizing symbionts in B. azoricus gills (Halary et al, 2008). This flexibility is thought to be a host adaptation to cope with its heterogeneous and highly variable environment (Boutet et al, 2011). Despite the extensive research done on bathymodiolin symbiosis, the underlying molecular mechanisms that govern this symbiosis are largely unknown.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA of both mussel and bacteria was extracted together from gill tissue and muscle (used as a negative control in real-time PCR amplification) using a CTAB/PVP extraction procedure and the relative quantity of symbionts was estimated by real-time PCR amplification using 16S specific primers according to the protocol described in Boutet et al, 2011. All experiments were carried out using a Chroma4 thermal cycler (Bio-Rad Laboratories Inc, Hercules, CA) and 1X ABsolute TM QPCR SYBR® Green mix (ABgene, Epsom, UK), 70 nM of each primer, and diluted DNA (2.5 ng) in a final volume of 10 μl.…”
Section: Symbiont Ratio Determinationmentioning
confidence: 99%